Modeling, Simulation and Control of An Omnidirectional Mobile Manipulator Robot - María José Mendoza Salazar, Martha Ximena Dávalos Villegas, María de Lourdes Palacios Robalino (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Manipulator robots are the most representative robots in the industrial, medical, service and security sectors; together with mobile robots, they constitute mixed robots that facilitate various tasks in these fields. The points of interest of these robots are kinematic modeling, control, planning, and simulation, hence the importance of their study. The present study aims to obtain the mathematical model for controlling an omnidirectional mobile manipulator robot and its implementation in simulation software. The agile methodology is used for the development of the control algorithms. In order to validate the obtained model. First, the basic behavioral tests are performed, then its movement is simulated by following predefined trajectories representing its behavior. In the simulation of movement in displacements, the mobile manipulator robot finds the position in the order z, y, x with the inverse kinematic model Newton method in a few iterations; on the other hand, with the inverse kinematic model Gradient method, it finds the position in the same order, but with more iterations than the other method; it is also shown the errors of the operating end before reaching the initial position, with results similar to those of the displacement. The results of this research open the possibility of performing different simulations, which allow evaluating the robot’s initial conditions and selecting the best ones to optimize resources.